Maize leaf phytotoxicity and grain yield are affected by nitrogen source and application method - Vargas, Vitor P.; Sangoi, Luis; Ernani, Paulo R.; Picoli, Gilmar José [UNESP]; Cantarella, Heitor (Amer Soc Agronomy, 2015)
Nitrogen fertilizer broadcast application over maize (Zea mays L.) is becoming more common as narrow row spacing is adopted and larger fields are cultivated. The contact of N fertilizers with plant leaves can partially damage leaf tissues and consequently affect crop yield. This study was conducted to evaluate the effect of source, method, and time of application of N fertilizer on maize leaf area and grain yield. A field trial was conducted in Brazil during two growing seasons. Urea (UR) and ammonium nitrate (AN) were applied at V5 and V10 maize growth stages broadcasted over the canopy or banded on the soil at a rate of 200 kg N ha(-1). Solid fertilizers were broadcasted over dry and wet leaves whereas for applications to the soil solid fertilizers or solutions were used. In the first season, broadcasting AN reduced the leaf area at silking by 15.7% compared to soil application regardless of leaf moisture. In the following year, broadcasting AN reduced by 7.5% the leaf area at silking compared with UR. In the first growing season, the grain yield with UR was 10.1% greater than that with AN when both fertilizers were broadcasted. In the second season for the same application method, the grain yield from crops fertilized with UR was 32% higher than those where AN was used. In addition, the yield was 18% greater when fertilizers were applied to the soil than when they were broadcasted. Broadcasting N fertilizers causes leaf phytotoxicity and may decrease grain yield, especially when AN is used.